FENOMENA REMAJA DALAM MASA TRANSISI - Annisa Tri Utami; Erfahmi Erfahmi (Universitas Negeri Padang, 2020)
The purpose of the creation of this final work is to visualize the phenomenon of adolescents in the transitional period that was raised into contemporary style paintings. The method of creating works through several stages including: preparation, elaboration, synthesis, realization of concepts, and completion stages. The ten works with the theme of social problems whose source of ideas come from the deviant behavior of adolescents who are experiencing the process of searching for identity. This work is visualized in a contemporary painting style that displays the deviant behavior and delinquency of adolescents who are affected by the internal and external factors of the teenager such as promiscuity, smoking, drugs, drinking, pornography, and others. As for the titles of the ten works including: Hold Control, Play Glue, Viral Desire, As a result of damage, Dinner, Misuse, Bullying, My Gift, May Be Adult, and Loner.Keywords: Teenage Phenomenon, Painting